Atmospheric flow field models applicable for aircraft endurance extension - R. A. G. Bencatel (2013)
We present a survey of atmospheric flow field phenomena models. The studied models are selected for their potential use toward extended aircraft endurance. This work describes several flow field phenomena, i.e., air flow currents and flow velocity variations. In particular, we discuss wind shear, thermal updrafts, and gusts. We study several wind shear models, such as the Surface, Layer, and Ridge Wind Shear models, comparing their characteristics. We also describe and compare thermal updraft models, such as the Chimney and the Bubble Thermal models. To close, we review different gust models. Throughout this work, we studied several existing models, but we also introduce new ones and improved versions of existing ones. The Bubble Thermal, Layer Wind Shear, and the Ridge Wind Shear models are examples of the new models presented. Furthermore, we present the Chimney Thermal model improvements, which take into account the phenomenon interaction with the prevailing winds.